THE AUTHORITY RECONSTRUCTION OF JUDGES IN DETAINING CHILDREN BASED ON THE JUSTICE VALUE - Agus Sugiarto; Asep Hermawan; Yanto Irianto (UNISSULA, 2023)
The purpose of this study is to determine the Authority Reconstruction of Judges in Detaining Children with the Justice Value. This research uses a normative approach. The resulting research states that the authority of judges including Appellate Judges or High Court Judges in detaining defendants is contrary to the principle of presumption of innocence, detention is the realm of presumption of guilt which can only be used by investigators and public prosecutors, if the judge is burdened with the authority to carry out detention, then The judge is no longer independent, because in his decision he will take into account the detention that has been carried out, even the detention carried out by the judge is within his authority, The ideal reconstruction of the judge's authority in carrying out detention based on the principle of presumption of innocence and the value of justice, is to revoke the judge's authority to detain the defendant and delegate it to the public prosecutor.